Atención ética en enfermería quirúrgica, promoviendo la autonomía del paciente en el perioperatorio: revisión sistemática - Chiles Cevallos, Diego Fernando (2025)
Nursing staff working in surgical areas consider it of utmost interest to instill an ethical approach to surgical care, promoting patient autonomy during the perioperative period. Objective: To analyze interventions in ethical care in surgical nursing, focusing on the promotion of patient autonomy during the perioperative period, through a systematic review. Methodology: A review of different articles published between 2021 and 2024 in various databases such as: Scielo, Elsevier, Pubmed, Dialnet, Research Gate, University Repositories and Google Scholar, including doctoral degree works, where 80 sources were integrated and applying inclusion and exclusion criteria based on the PRISMA methodology such as: relevance of the topic, date of publication, type of study and quality of methodology, in addition, 21 paramount studies for this research were included. Results: The results showed the importance of sound and humanized ethics in nursing practice, highlighting the need to balance technical knowledge with the development of emotional and communicative skills. Informed consent should be seen as a dynamic and adaptive process that respects patient autonomy and promotes a trusting relationship between doctor and patient. Conclusion: This research highlights the need for improved communication and ongoing ethics training that are essential to ensure that informed consent is implemented effectively and meaningfully, improving the quality of medical care.